Practical Ways to Ensure Educational Justice for Subaltern Students of Nepal - Karki, Mahendra Kumar (AMC Journal, 2020)
This article aims at sharing knowledge about educational justice for subaltern students of Nepal. The descriptive research design was used for the study. The secondary sources of data were educational document and online materials. The sample was limited to the only concept educational justice for subaltern students of Nepal and global perspectives. With few exceptions, students of the subaltern community obtain low score in school, college, and university. The article applies to some theories like as cultural, ethical, and pedagogical. Research also mentions theoretical, philosophical, and practical ways to ensure educational justice to the subaltern students of Nepal. Education plays a vital role to being a subaltern. Subaltern students have no access to achieve the facilities and opportunities provided by the government because of their different causes and unequal distribution of resources. They are being subaltern because they have no more representation in schooling system. The data used in study is qualitative which are collected from educational philosophical and related to Subaltern textbook, journal and National and international educational report. Likewise, various an educational document, Ministry of Education Nepal. Analytical and descriptive methods are applied in this study.